2013
DOI: 10.1186/1472-6882-13-234
|View full text |Cite
|
Sign up to set email alerts
|

Selaginella tamariscina extract suppresses TPA-induced invasion and metastasis through inhibition of MMP-9 in human nasopharyngeal carcinoma HONE-1 cells

Abstract: BackgroundNasopharyngeal carcinoma (NPC) is known for its high incidence of neck lymph node metastasis, which represents poor prognosis. The present study aimed to examine the anti-metastatic properties of Selaginella tamariscina extract (STE) in human nasopharyngeal carcinoma HONE-1 cells in vitro.MethodsCell viability was examined by MTT assay, whereas cell motility was measured by invasive, migration and would healing assays. Real-time PCR, and promoter assays confirmed the inhibitory effects of STE on matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…Other innovative therapeutic approaches, such as targeted anticancer treatment with biological antibodies or newly identified naturally occurring chemicals, are needed to improve treatment outcomes. A large body of experimental evidence shows that herbal medicines are beneficial in the treatment of cancers (Newman et al, 2002), including our previous study on the antimetastatic effect of Selaginella tamariscina extract on NPC cells (Hsin et al, 2013). Recently, P. linteus has been reported to be a promising candidate as an alternative anticancer agent that acts synergistically with existing antitumor drugs (Zhu et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Other innovative therapeutic approaches, such as targeted anticancer treatment with biological antibodies or newly identified naturally occurring chemicals, are needed to improve treatment outcomes. A large body of experimental evidence shows that herbal medicines are beneficial in the treatment of cancers (Newman et al, 2002), including our previous study on the antimetastatic effect of Selaginella tamariscina extract on NPC cells (Hsin et al, 2013). Recently, P. linteus has been reported to be a promising candidate as an alternative anticancer agent that acts synergistically with existing antitumor drugs (Zhu et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…This study revealed that TCE suppressed TPA‐induced invasion and metastasis through the inhibition of MMP‐9 and ERK1/2 phosphorylation in human cervical cancer cells. TPA, is a small molecule drug, as a tumor‐promoting agent in various cancer cell lines . However, Zhu et al reported that TPA has been established as an anti‐tumorigenic drug in liver cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…According to the manufacturer's instructions, 2 μg of RNA was reverse‐transcribed into cDNA using the SuperScript III First‐Strand Synthesis Supermix kit (Invitrogen, Carlsbad, California). The mRNA levels of MMP‐9 were examined through reverse transcription‐polymerase chain reaction (RT‐PCR) and real‐time PCR as previously described …”
Section: Methodsmentioning
confidence: 99%
“…The FAK and Src activation is capable of modulating cell migration and invasion [18, 19, 30]. Our previous study revealed that FAK phosphorylation was involved in caffeic acid phenethyl ester-inhibited oral cancer cell metastasis [21] and WISP1-induced OSCC angiogenesis [31].…”
Section: Discussionmentioning
confidence: 99%